(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
This study examines how to include technology advancement into energy-economy models and how that affects long-term energy demand predictions. The models range from an exogenous yearly change in energy efficiency to an endogenous explanation of energy technology innovation. Technological advancement is frequently cited as the primary factor to the differences in energy demand forecasts from various models. Endogenous growth and industrial organization theories have significant implications for efforts to endogamies technical innovation and the diffusion of new energy technologies. The article surveys several theoretical and empirical theories of technological development. This study compares two different models of household energy consumption in Denmark. Two macro econometric models, one for Denmark and the other for the US, are compared. The two models’ energy demand projections vary, and it’s up to us to prove that the assumptions about technological development are the cause. The forecast relies on assumptions regarding energy efficiency improvements in older models. Vintage modelling is less essential for long-term forecasts. Long term vintage modelling has a constraint that explains some of the differences in predictions between the two kinds of models. The current electric appliance model does not properly represent the new energy-consuming equipment that will be available in the future. This category has to be modelled more thoroughly for long term predictions.